Pendidikan Islam Multikultural dalam Penguatan Budaya Masyarakat Majemuk di Pesantren Darul Ma'arif Nahdhatul Ulama Rejang Lebong - Faham Syah; Wiwik Damayanti; Sutarto Sutarto; Deri Wanto (UIN Fatmawati Sukarno Bengkulu, 2026)
Abstract: The diverse community within the pesantren (Islamic boarding school) faces significant challenges in maintaining social cohesion amidst a plurality of religions, cultures, customs, languages, and ethnicities. This study aims to map and analyze multicultural Islamic education as a means of strengthening the diverse community culture at the Darul Ma’arif Nahdlatul Ulama pesantren in Rejang Lebong. It employs a qualitative method based on the analysis of the pesantren’s operational documents, curriculum, and institutional publications (covering the 2021–2025 period). Research findings indicate that multicultural Islamic education at the Darul Ma'arif NU Rejang Lebong Islamic Boarding School (Pondok Pesantren) has been normatively adopted into the institution's vision and orientation, which are characterized by both traditional and pluralistic elements. Multicultural Islamic educational values encompassing cultural, ethnic, religious, and social diversity serve as the foundation for creating a learning environment defined by equality, inclusivity, democracy, tolerance, moderation, justice, and intercultural dialogue; these values are realized through social habituation, the exemplary conduct of the kyai (religious leader), and extracurricular activities. Thus, it can be concluded that multicultural Islamic education plays a decisive role in strengthening pluralistic culture in Indonesia. Consequently, it is suggested that the integration of multicultural values into the formal pesantren curriculum specifically regarding educators' capacity to facilitate dialogic and inclusive learning, students' digital literacy, and cross-institutional partnerships requires further enhancement to strengthen the culture of a pluralistic.Keywords: Multicultural Islamic Education, Strengthening Pluralistic Community Culture, Darul Ma'arif Nahdlatul Ulama Islamic Boarding School, Rejang Lebong. Abstrak: Budaya masyarakat pesantren yang majemuk menghadapi tantangan serius dalam menjaga kohesi sosial di tengah pluralitas agama, budaya, adat istiadat, bahasa, suku dan etnis. Tujuan penelitian untuk memetakan dan menganalisis pendidikan Islam multikultural dalam penguatan budaya masyarakat majemuk di pesantren Darul Ma’arif Nahdhatul Ulama Rejang Lebong. Menggunakan metode kualitatif berbasis analisis dokumen operasional pesantren, kurikulum, dan publikasi institusional (periode 2021–2025). Hasil penelitian menunjukkan bahwa pendidikan Islam multikultural di Pondok Pesantren Darul Ma'arif NU Rejang Lebong telah diadopsi secara normatif dalam visi dan orientasi kelembagaan pesantren yang tradisional dan majemuk. Nilai-nilai pendidikan Islam multikultural seperti keberagaman budaya, etnis, agama, dan latar belakang sosial sebagai landasan untuk menciptakan lingkungan belajar yang setara, inklusif, demokratis, toleran, moderat, keadilan, dan dialog antar budaya diwujudkan melalui pembiasaan sosial, keteladanan kyai, dan praktik ekstrakurikuler. Dengan demikian dapat disimpulkan bahwa pendidikan Islam multikultural menjadi faktor penentu dalam penguatan budaya majemuk di Indonesia. Sehingga dapat disarankan integrasi nilai multikultural dalam kurikulum formal pesantren seperti kapasitas pendidik dalam mengelola pembelajaran dialogis dan inklusif, literasi digital peserta didik, dan kemitraan lintas lembaga masih perlu ditingkatkan dalam penguatan budaya masyarakat majemuk.Kata kunci: Pendidikan Islam Multikultural, Penguatan Budaya Masyarakat Majemuk, Pesantren Darul Ma'arif Nahdhatul Ulama Rejang Lebong.